Beauty and productivity in academic publishing - Kseniya Bortnikova (Charles University in Prague, Institute of Economic Studies (IES), 2023)
Academic publishing represents a field in which the opportunity for discrimination based on appearance should be limited since intellectual skills must play a key role. In this work, I document the beauty effect for economic scholars. Using unique data on academics who published their research papers in economic journals in 2017 I test whether more attractive academics are more productive. I found evidence that appearance is positively and significantly associated with the success of research output as measured by the higher number of citations. However, the effect magnitude is rather small, and it becomes even smaller when I control for the ranking of the Ph.D. granting institution.
Keywords: C83; J3; J7; M51; 330; Beauty bias; productivity; discrimination; academic publishing